Al-Sifat al-Ilahiyyah 'Inda Muhammad Sa'id Ramadhan al-Buthi - Abdul Mun'im (Universitas Darussalam Gontor, 2018)
The debate around Islamic belief (aqidah) among mutakallimun has never been resolved until today, especially about the attributes of God. The problem is on the manhaj used by each of them. Some of them argue that establishing the attributes of God must be based on naqli exponent only, while others argue that the naqli exponent only is not enough, but it still requires aqli exponent, so there is no tasybih (likeness) between God and His creatures. In addition, there are those who argue that it is enough to use aqli exponent only, so that there is no any indication of deciding qadim attribute to other than God. So this problem needs a serious study of the fundamental aspects of aqidah to establish the attributes of God with manhaj according to the understanding of Ahlussunnah wal Jama'ah. Therefore, the researcher discusses the thoughts of Muahmmad Sa'id Ramadhan Al-Buthi regarding the characteristics of God which formulates both exponents of naqli and aqli in each portion.